ENGINEERING STUDENTS’ BLENDED LEARNING IN HIGHER EDUCATION - Ahrens, Andreas; Zaščerinska, Jeļena; Andreeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Blended learning in higher education has already become an indispensable tool in both university staff and students’ daily life. A number of definitions of blended learning have been developed. However, these definitions mostly focus on the synergy of traditional and online instruction, thereby these definitions lack its main notion - blended learning. These othersided definitions do not contribute to the qualitative blended learning for the improvement of students’ learning achievements. Aim of the present paper is to analyze and work out the definition of blended learning underpinning analysis of quality of blended learning for the improvement of students’ learning achievements. The meaning of the key concepts of blended learning and students’ learning achievements is studied. Moreover, the logical chain of analysis is shown: blended learning → students’ learning achievements → empirical study within a multicultural environment. The results show that students’ learning achievements after having been implemented the blended learning process have been enhanced. Directions of further research are proposed. The novel contribution of the paper is the definition of blended learning worked out by the paper’s authors.